Modelling and analysis for inverted pendulum/ Rosmawati Othman - Othman, Rosmawati (1997)
This project is intended to solve a complex nonlinear control problem. The problem is to come up with an automatic means of controlling the back and forth movement of a cart in order to balance the inverted pendulum and guide the cart to the center of a tooth track in a vertical pole attached at its base to the cart. From the practical, two experimental results are attached refer to Linear servo motor experiment which involved two controllers, PD and PID and Linear motion experiment by using foil state feedback with and without integrator controller considering the four observable parameter of the inverted pendulum system referred to the optimal gain of K. From the observation found PID more efficient to improve the stability and the transient response of the system than PD controller and the state feedback with integrator more accurate and speed up the response. The key, is to give readers plenty of examples, each in sufficient detail so that the student can assimilate the information and use the accumulated experience of others to create his/her own applications.